The Influence of Motivation and Compensation on Employee Job Satisfaction at PT Bank Syariah Indonesia at KCP Cikupa Tangerang - Khotimah, Khusnul; Sukarya, Yaya; Azhari, Muhammad Zakky (IJOSPOL - International Journal of Social, Policy and Law, 2026)
The research entitled The Influence of Motivation and Compensation on Employee Job Satisfaction at PT Bank Syariah Indonesia at KCP Cikupa Tangerang is motivated by the importance of motivation and compensation in influencing employee job satisfaction. The research aims to determine the influence of motivation and compensation partially and simultaneously on employee job satisfaction. The research sample consisted of 24 employees. The method used was quantitative with primary data collection through questionnaires and secondary data from relevant books and journals and company documentation. The results of the study showed that motivation did not have a significant effect partially, while compensation had a significant effect partially. Simultaneously, both had a significant effect on employee job satisfaction.